PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN METODE SENTRIFUGASI (Jurnal Teknologi Pangan, 2013)
Virgin Coconut Oil (VCO) is the oil produced from fresh coconuts. Unlike the ordinary coconut  oil,  Virgin  Coconut  Oil  (VCO)  is  produced  not  by the  addition  of  chemicals  or processes  that  use  high  heat.  Virgin  Coconut  Oil  (VCO)  beneficial  to  health,  this  is  because Virgin Coconut Oil (VCO) contains many medium chain fatty acids (Medium Chain Fatty Acid /  MCFA).  MCFA  are  most  in  the  Virgin  Coconut Oil  (VCO)  is  Lauric  acid  (Lauric  Acid). Properties  that  is  easily  absorbed  MCFA  will  increase  metabolism.  The  addition  of  energy produced  by  the  metabolism  of  this  produces  stimulating  effects  in  the  human  body  thereby increasing the level of energy produced.  Core  processes  in  the  manufacture  of  Virgin  Coconut  Oil  (VCO)  is  located  on  the separation of oil from water and protein. Many obstacles must be faced for separating oil from water  and  proteins,  such  as  in  the  fermentation  process,  the  separation  process takes  a  long time to get the Virgin Coconut Oil (VCO). While the centrifugation, the separation is done by utilizing the weight of the lighter oil. Although I do not require centrifugation long time but the way it has in the purity of the product constraints.  This research was conducted by using coconut cream from coconut milk is silenced for 3  hours.  Then  the  cream  is  incorporated  into  the  instrument  with  speed  centrifuges  spin 600,700,800,900 and 1000 rpm with vaiasion  times very; 30, 45, 60.75 and 90 minutes after that  coconut  cream  layer  divided  into  3  layers  of  oil  that  is,  the  middle  layer  of  protein (blondo)  and  next  underwater  layer  silenced  for  8,10,12,14,  and  16  hours  .  The  results  of virgin  coconut  oil  (VCO)  is  obtained  and  then  analyzed  with  the  parameters  water  content, protein content, Lauric acid, color and odor.  From the research, obtained the best conditions of rotational speed centrifuges at 1000 rpm and centrifuges turnaround time 90 minutes and 8 hours stagnand time with the quality of Virgin  Coconut  Oil  (VCO)  which  produced  yield:  Lauric  acid  yield  of  36.67%  and  52.23% results.Keywords: sentrifuge, coconut cream,,% yield results, VCO